2005
DOI: 10.4161/cc.4.10.2054
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic Tail domain of Human Cdc34 is Required for p27Kip1 Ubiquitination and Complementation of a cdc34 Temperature Sensitive Yeast Strain

Abstract: Human Cdc34 is an ubiquitin conjugating enzyme or E2 that ubiquitinates substrates including p27 Kip1 , IκBα, Wee1 and MyoD. Cdc34 possesses a core catalytic domain encoding the active site cysteine and an acidic tail domain within the carboxyl terminal 36 amino acids. Studies suggest that Cdc34 is phosphorylated in mammalian cells at 5 potential residues within the tail domain. In order to study the biological significance of the Cdc34 acidic tail domain and the possible significance of phosphorylation within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Previous studies have shown that the full-length hCdc34 but not its truncated form (hCdc34 ) is able to support growth in the temperaturesensitive cdc34-2 yeast strain at non-permissive temperature (37°C) when the endogenous Cdc34 is disabled (16). As shown (Fig.…”
Section: Non-labeled Proteinsmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies have shown that the full-length hCdc34 but not its truncated form (hCdc34 ) is able to support growth in the temperaturesensitive cdc34-2 yeast strain at non-permissive temperature (37°C) when the endogenous Cdc34 is disabled (16). As shown (Fig.…”
Section: Non-labeled Proteinsmentioning
confidence: 61%
“…5 The abbreviations used are: hCdc34, human Cdc34; Bistris propane, able to complement growth defects by a temperature-sensitive cdc34 mutant yeast strain (cdc34-2, harboring the G58R mutation) at non-permissive temperature (15,16 , respectively (5,16). Previous studies have shown that the yeast Cdc34 C-terminal tail is required for the G 1 -to-S phase transition of the cell cycle and that this activity is probably mediated by the ability of the yeast Cdc34 C terminus to interact with SCF (17,18).…”
mentioning
confidence: 99%
“…The last 37 amino acids of IE2-86 have been shown to contain a transferable transactivation domain that is required for transactivation, autoregulation, and DNA binding (4,13,30). The acidic domains of other proteins were important for ubiquitination reactions (6,42), suggesting the possibility of a role for this region of IE2-86 in catalysis. An IE2-86-mdm2 complex might recruit another coactivator(s), corepressor(s), kinase(s), or component(s) responsible for protein degradation by synergy of its zinc finger/LIM and acidic domains.…”
Section: Discussionmentioning
confidence: 99%
“…20 Yeast Cdc34, human CDC34 and its homologous CDC34B are phosphorylated by CK2. [21][22][23][24][25][26] The CK2 phosphorylation sites of human CDC34 are localized within the C-terminal 36 amino acids (Ser203, Ser222, Ser231, Thr233, Ser236). 25,26 Similarly, yeast Cdc34 is phosphorylated by CK2 on the C-terminal tail (Ser207, Ser216, Ser282).…”
Section: Introductionmentioning
confidence: 99%